Interferon-β decreases LPS-induced neutrophil recruitment to cardiac fibroblasts - Renatto Anfossi; Renatto Anfossi; Raúl Vivar; Raúl Vivar; Pedro Ayala; Fabiola González-Herrera; Claudio Espinoza-Pérez; José Miguel Osorio; Mauricio Román-Torres; Samir Bolívar; Guillermo Díaz-Araya; Guillermo Díaz-Araya (Frontiers in Cell and Developmental Biology, 2023)
Introduction: Cardiac fibroblasts (CF) are crucial cells in damaged heart tissues, expressing TLR4, IFN-receptor and responding to lipopolysaccharide (LPS) and interferon-β (IFN-β) respectively. While CF interact with immune cells; however, their relationship with neutrophils remains understudied. Additionally, theimpact of LPS and IFN-β on CF-neutrophil interaction is poorly understood.Methods: Isolated CF from adult rats were treated with LPS, with or without IFN-β. This study examined IL-8 secretion, ICAM-1 and VCAM-1 expression, and neutrophil recruitment, as well as their effects on MMPs activity.Results: LPS triggered increased IL-8 expression and secretion, along with elevated ICAM-1 and VCAM-1 expression, all of which were blocked by TAK-242. Pre-treatment with IFN-β countered these LPS effects. LPS treated CF showed higher neutrophil recruitment (migration and adhesion) compared to unstimulated CF, an effect prevented by IFN-β. Ruxolitinib blocked these IFN-β anti-inflammatory effects, implicating JAK signaling. Analysis of culture medium zymograms from CF alone, and CF-neutrophils interaction, revealed that MMP2 was mainly originated from CF, while MMP9 could come from neutrophils. LPS and IFN-β boosted MMP2 secretion by CF. MMP9 activity in CF was low, and LPS or IFN-β had no significant impact. Pre-treating CF with LPS, IFN-β, or both before co-culture with neutrophils increased MMP2. Neutrophil co-culture increased MMP9 activity, with IFN-β pre-treatment reducing MMP9 compared to unstimulated CF.Conclusion: In CF, LPS induces the secretion of IL-8 favoring neutrophils recruitment and these effects were blocked by IFN-. The results highlight that CF-neutrophil interaction appears to influence the extracellular matrix through MMPs activity modulation.